Modelling the potential impact of mask use in schools and society on COVID-19 control in the UK - Panovska-Griffiths, J; Kerr, CC; Waites, W; Stuart, RM; Mistry, D; Foster, D; Klein, DJ; Viner, RM; Bonell, C (Springer Nature, 2021)
As the UK reopened after the first wave of the COVID-19 epidemic, crucial questions emerged around the role for ongoing interventions, including test-trace-isolate (TTI) strategies and mandatory masks. Here we assess the importance of masks in secondary schools by evaluating their impact over September 1-October 23, 2020. We show that, assuming TTI levels from August 2020 and no fundamental changes in the virus's transmissibility, adoption of masks in secondary schools would have reduced the predicted size of a second wave, but preventing it would have required 68% or 46% of those with symptoms to seek testing (assuming masks' effective coverage 15% or 30% respectively). With masks in community settings but not secondary schools, the required testing rates increase to 76% and 57%.